Identification of Novel Serum Autoantibodies for Differential Diagnosis of Autoimmune Pancreatitis and Pancreatic Ductal Adenocarcinoma. Issue 9 (October 2016) - Felix, Klaus; Hauck, Oliver; Schnölzer, Martina; Kempf, Tore; Warnken, Uwe; Schneider, Kathrin; Bergmann, Frank; Fritz, Stefan; Werner, Jens
Abstract : Objectives: The lack of specific biochemical markers is a major drawback for the diagnosis of autoimmune pancreatitis (AIP). The aims were to characterize the autoantibody profiles in AIP and pancreatic ductal adenocarcinoma (PDAC) and to identify circulating autoantibodies that could be diagnostic markers differentiating PDAC and the AIP subtypes. Methods: Tissue lysates obtained from the resected pancreas of patients with AIP and patients with PDAC were separated by 2-dimensional polyacrylamide gel electrophoresis subsequently immunoblotted with autologous sera. The immunoreactive spots were subjected to nanoscale liquid chromatography–electrospray ionization tandem mass spectrometry to identify serum autoantibodies to tissue-derived autoantigens associated with AIP and PDAC. Autoantibody concentrations for selected autoantigens were assessed by enzyme-linked immunosorbent assays. Results: A total of 115 immunoreactive spots were identified by 2-dimensional polyacrylamide gel electrophoresis/immunobloting. Nanoscale liquid chromatography–electrospray ionization tandem mass spectrometry–based analysis revealed 68 autoantigens in AIP, 26 in PDAC, and 21 present in both diseases. Assessment of 13 selected AIP autoantibody serum levels revealed that 7 of them had significantly higher titers in AIP versus PDAC. IgG-directed against transaldolase could significantly differentiate between the 2 AIP subtypes. Conclusions: The novel panel of AIP autoantibodies is promising to supplement the predictive tests for AIP of the currently known autoantigens and represent a basis for a combined blood test to differentiate AIP from PDAC in the future.